Twenty-Four Hour Live Chat Feature and Customer Satisfaction - Sari, Maemunah Nurmaya; Gracia, Lucia Ristania (International Journal of Applied Management and Business, 2024)
Purpose –This paper wants to describe the e-service quality of customer support in handling crypto asset consumer problems using the 24-hour live chat feature, and an overview of customer satisfaction ratings at PT Akunku Dotcom Indonesia Methodology/approach –The survey was conducted on 100 Reku friend respondents who had interacted with customer support via the 24-hour live chat feature. The instrument used is a questionnaire with 4 Likert scales and customer satisfaction rating data. The assessment of e-service quality is presented in the form of an average answer score and the level of agreement between Reku friends. Findings –E-Service Quality through the 24 Hour Live Chat Feature on Reku received a positive response from Reku users with an agreement rate of almost 90%. Reku Indonesia's Customer Satisfaction Rating is dominated by the Good Rate category. Both the Good Rate and Bad Rate sections are mostly influenced by Customer Support services. Novelty/value –Customer support needs to provide a sense of security to customers of digital products such as crypto assets, through maximum e-service quality, so that this can have an impact on maximum customer satisfaction ratings too